2018 Sensor Data Fusion: Trends, Solutions, Applications (SDF) 2018
DOI: 10.1109/sdf.2018.8547047
|View full text |Cite
|
Sign up to set email alerts
|

LIDAR Extended Object Tracking of a Maritime Vessel Using an Ellipsoidal Contour Model

Abstract: Extended object tracking (EOT) have numerous applications and can be integrated in autonomous systems like self-driving cars or autonomous surface vehicles. These systems can be improved by using robust tracking algorithms that accurately estimate the position, velocity and extent of surrounding targets from sensor data. EOT is relevant for many different sensors, and the methods developed are based on which sensor that is used. In this thesis LIDAR is used to track a single target in a maritime environment th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…The traditional vessel tracking system is usually implemented by satellite tracking technology [33,34]. The satellite tracking technology needs to have a GPS receiver on the vessel to receive the signal from the satellite and return the signal to the ground control center [35], which has the advantage of wide coverage but the signal may be interfered with.…”
Section: Vessel Trackingmentioning
confidence: 99%
“…The traditional vessel tracking system is usually implemented by satellite tracking technology [33,34]. The satellite tracking technology needs to have a GPS receiver on the vessel to receive the signal from the satellite and return the signal to the ground control center [35], which has the advantage of wide coverage but the signal may be interfered with.…”
Section: Vessel Trackingmentioning
confidence: 99%
“…Detailed reviews on extent approximation methods can be found in [5,14,15]. Ellipses have so far been the most favored basic shape to approximate vessels' extents in maritime applications, where we represent the length and width by means of the ellipse's axes and the true heading by the ellipse's orientation [16][17][18][19]. Traditional methods for elliptical target tracking are based on the Random Matrix Method (RMM) framework, where a target's kinematic state is modeled as a Gaussian distribution and its extent by a Wishart distribution, which is represented using an Symmetric and Positive Definite (SPD) matrix [6,[20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…A method for dealing with obstacle detection in LiDAR and cameras is proposed in (Faggioni et al, 2022).Figure 1 shows a possible application of the discussed procedure in a multi-sensor data fusion perceptive system. In paritcular, obstacles are detected in the LiDAR point cloud and the acquired targets are tracked by adopting a low computational customized method, instead of the probabilistic approaches generally employed (Ruud et al, 2018) (Lee et al, 2010). To simplify the handling of the problem, tracking is performed on the centroids of the point clouds; such an approach is often adopted to decrease the computational cost (Fang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%